Cogging Torque Mitigation using the Unequal Rotor Slot Arcs Method based on Magnetic Permeance Distribution for Flux-Switching Machines - Emrah Cetin (Journal of Electromagnetic Engineering and Science)
Permanent magnet machines, such as flux-switching permanent magnet (FSPM) machines, are characterized by cogging torque, which must be addressed because it leads to torque fluctuations. With permanent magnetics usually buried in the stator winding of FSPM machines, cogging torque occurs due to the mutual effects of the stator magnetic field and the rotor ferromagnetic material. In this study, the unequal rotor slot arc (URSA) method, which manipulates the magnetic permeance distribution (MPD) in the airgap, is employed to diminish the cogging torque. Furthermore, to demonstrate the effects of MPD, a mathematical model is developed. Parametric optimization is implemented to obtain the optimal cogging torque value that also maintains a convenient average torque output. The results show that the proposed URSA technique significantly reduces cogging torque.